Cognitive disorders in Parkinson's disease: Confirmation of a spectrum of severity. Issue 11 (November 2015) - Dujardin, Kathy; Moonen, Anja J.H.; Behal, Hélène; Defebvre, Luc; Duhamel, Alain; Duits, Annelien A.; Plomhause, Lucie; Tard, Celine; Leentjens, Albert F.G.
Abstract: Introduction: Clinical presentation and progression of cognitive disorders in Parkinson's disease (PD) is heterogeneous. Our objective was to confirm prospectively a previous exploratory cluster analysis based on retrospective data that identified five cognitive phenotypes in PD. Methods: A model-based confirmatory cluster analysis was conducted on the results of neuropsychological tests administered in 156 PD patients from two European movement disorder centers (Lille, n = 81; Maastricht, n = 75). The number of clusters was determined on the basis of statistical criteria as well as clinical plausibility. A factorial discriminant analysis assessed the quality of the clusters' separation. Results: A five-cluster model was statistically superior and clinically the most relevant. These clusters can be described as follows: 1) cognitively intact patients with high level of performance in all cognitive domains (25.64%), 2) cognitively intact patients slightly slower than those in cluster 1 (26.92%), 3) patients with deficits in executive functions (37.18%), 4) patients with severe deficits in all cognitive domains, particularly executive functions (3.20%), 5) patients with severe deficits in all cognitive domains, particularly working memory and recall in verbal episodic memory (7.05%). The groups differed in terms of age, apathy and frequency of hallucinations that were all higher in the clusters with cognitive deficits, and the duration of formal education was lower in those groups. Conclusion: We confirm our previous exploratory analysis. Cognitive disorders in PD patients are heterogeneous and can be separated in five clusters ranging from patients with performance in the normal range to patients with severe disorders in all cognitive domains. Highlights: Cognitive disorders in PD patients are heterogeneous. We confirm that there are five clinical presentations of cognitive disorders in PD. Slowness, Stroop errors and semantic fluency were the most discriminant variables.